2019
DOI: 10.3892/br.2019.1238
|View full text |Cite
|
Sign up to set email alerts
|

Levels of nitric oxide metabolites, adiponectin and endothelin are associated with SNPs of the adiponectin and endothelin genes

Abstract: Adiponectin, endothelin and nitric oxide (NO) are major regulators of vascular function. An imbalance of vasoactive factors contributes to the onset and progression of atherosclerosis. Various single nucleotide polymorphisms (SNPs) are considered to be risk factors for coronary heart disease. However, the molecular mechanisms of their associations with the components of endothelial dysfunction are poorly understood. In the present study, rs17366743, rs17300539, rs266729, rs182052 and rs2241766 SNPs of the adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Because, superoxide anion which is the main oxygen species reacts with nitric oxide radical forming peroxynitrite -a free radical, causing oxidative stress and cellular damage. Gumanova et al (24) in their study found that higher levels of NO are significantly associated with coronary lesions though, some studies reported increased activity of SOD in ischemic heart disease patients (25). On the other hand, other studies similar to our study revealed decreased activity of SOD (19,21,26).…”
Section: Discussionmentioning
confidence: 99%
“…Because, superoxide anion which is the main oxygen species reacts with nitric oxide radical forming peroxynitrite -a free radical, causing oxidative stress and cellular damage. Gumanova et al (24) in their study found that higher levels of NO are significantly associated with coronary lesions though, some studies reported increased activity of SOD in ischemic heart disease patients (25). On the other hand, other studies similar to our study revealed decreased activity of SOD (19,21,26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intron-retention (not removed introns) has recently garnered attention as a major component of the global alternative splicingmediated regulation and mRNA expression regulation, which are part of many mammalian programs of gene expression [44]. Indeed, Gumanova et al [45] reported the association between rs182052 and rs266729 ADIPOQ polymorphisms with adiponectin levels in men. Overall, these lines of evidence suggest that ADIPOQ polymorphisms may alter the expression levels and consequently adiponectin content.…”
Section: Discussionmentioning
confidence: 99%
“…Установлено, что высокая концентрация NOx >75 мкМнезависимый ФР сердечно-сосудистой смерти в течение 3-летнего периода наблюдения [65], ФР сердечно-сосудистой смерти в течение 8-летнего периода наблюдения у мужчин, и за этот же период -не связанный с полом ФР смерти от всех причин [66]. Полученные результаты согласуются с опубликованными позднее данными Фремингемского исследования [67], собственными данными авторов [68] и данными японских исследователей [69]. Кроме того, было обнаружено, что высокий уровень NOx ассоциирован с большим количеством хронических неинфекционных заболеваний, за исключением онкологических [70].…”
Section: перспективные кардиоспецифические биомаркеры циркулирующие суммарные нитрат и нитрит ионы (Nox) -фр сердечно-сосудистой смертиunclassified